NOTAS SOBRE A FORMAÇÃO DE UM SISTEMA TRANSNACIONAL DE ENSINO SUPERIOR - Benedito Martins, Carlos (Caderno CRH, 2015)
O presente artigo, tendo como referência analítica a relação reciproca entre processo de globalização e ensino superior, tem por objetivo abordar determinas transformações que estão ocorrendo no ensino superior nas sociedades contemporâneas. Apoiado numa bibliografia pertinente ao tema, o artigo salienta que, no contexto da globalização, o ensino superior não se confina mais nos limites das sociedades nacionais, mas transborda para além de suas fronteiras. Indica a emergência de determinados acontecimentos ocorridos nas últimas décadas que conduziram o ensino superior a atuar num espaço transnacional. As informações fornecidas pelo artigo tendem a indicar que, nas sociedades contemporâneas, o ensino superior vem adquirindo, cada vez mais, uma dimensão relacional, de tal modo que as universidades e seus respectivos países estão constantemente se comparando e competindo uns com os outros em busca de prestígio acadêmico no contexto internacional do ensino superior. Palavras-chave: Desterritorialização do ensino superior. Mobilidade acadêmica internacional. Rankings internacionais. World class University NOTES ON THE FORMATION OF A HIGHER EDUCATION SYSTEM TRANSNATIONAL Carlos Benedito Martins This article having as analytical reference the reciprocal relationship between globalization and higher education, aims to approach some changes that are taking place in higher education in contemporary societies. Supported by a pertinent literature to the subject, the article pointed out that in the context of globalization, higher education is not confined more within the national societies, but overflows beyond its borders. The article indicates the emergence of certain events that occurred in recent decades leading higher education to work in a transnational space. The information provided by article tend to indicate that in contemporary societies higher education is acquiring an increasingly relational dimension, so that universities and their respective countries are constantly comparing yourself and competing with each other in search of the academic prestige in the international context of higher education. Key words: Deterritorialization of higher education. International academic mobility. International rankings. World class university NOTES SUR LA FORMATION D’UN SYSTÈME D’ENSEIGNEMENT SUPÉRIEUR TRANSNATIONAL Carlos Benedito Martins Cet article, ayant comme référence analytique la relation réciproque entre la mondialisation et l’enseignement supérieur, vise à analyser les changements qui opèrent au enseignement supérieur dans les sociétés contemporaines. Soutenu par une bibliographie pertinente au sujet, l’article fait remarquer que dans le contexte de la mondialisation, l’enseignement supérieur ne se limite pas plus aux sociétés nationales, mais déborde au-delà de ses frontières. L’article indique l’émergence de certains événements qui se sont produits au cours des dernières décennies qui ont conduit l’enseignement supérieur à opérer dans l’espace transnational. Les informations fournies par l’article tendent à indiquer que, dans les sociétés contemporaines, l’enseignement supérieur acquiert une dimension plus relationnelle, de sorte que les universités et leurs pays respectifs sont constamment en comparaison et en concurrence les uns avec les autres, tous à la recherche du prestige académique dans le contexte international de l’enseignement supérieur. Mots Clés: Déterritorialisation de l’enseignement supérieur. La mobilité académique internationale. Les classements internationaux. L’université de classe mondiale. <small style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; background-color: #ffffff;">Publicação Online do Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; float: none; display: inline ! important; background-color: #ffffff;"> <br style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; background-color: #ffffff;" /> <br style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; background-color: #ffffff;" /> <small style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; background-color: #ffffff;">Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br<span style="color: #000000; font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; text-align: start; text-indent: 0px; text-transform: none; white-space: normal; widows: 1; word-spacing: 0px; font-family: Verdana,Arial,Helvetica; font-size: 12px; float: none; display: inline ! important; background-color: #ffffff;">